2017
DOI: 10.1128/aac.02256-16
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Oligoribonuclease Contributes to Tolerance to Ciprofloxacin by Regulating Pyocin Biosynthesis

Abstract: Bacterial oligoribonuclease (Orn) is a conserved 3=-to-5= exonuclease. In Pseudomonas aeruginosa, it has been demonstrated that Orn plays a major role in the hydrolysis of pGpG, which is required for cyclic-di-GMP homeostasis. Meanwhile, Orn is involved in the degradation of nanoRNAs, which can alter global gene expression by serving as transcription initiation primers. Previously, we found that Orn is required for the type III secretion system and pathogenesis of P. aeruginosa, indicating a role of Orn in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 52 publications
(55 reference statements)
0
18
0
Order By: Relevance
“…That enzyme was conserved in bacteria which has a 3'-5' exonuclease activity that break 2-5-nt RNA (nanoRNA) to mononucleotide. If Orn decreases, there will increase of nanoRNA and cyclic-di-GMP (C-di-GMP) that can decrease expression TTSS P. aeruginosa (Chen et al 2016, Chen et al 2017. C-di-GMP altered the amount of cAMP levels that induce expression of TTSS genes by cAMP reseptor protein Vfr (Chen et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…That enzyme was conserved in bacteria which has a 3'-5' exonuclease activity that break 2-5-nt RNA (nanoRNA) to mononucleotide. If Orn decreases, there will increase of nanoRNA and cyclic-di-GMP (C-di-GMP) that can decrease expression TTSS P. aeruginosa (Chen et al 2016, Chen et al 2017. C-di-GMP altered the amount of cAMP levels that induce expression of TTSS genes by cAMP reseptor protein Vfr (Chen et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial strains, plasmids and primers used in this study were listed in Table 1 (Furste et al, 1986; Hoang et al, 1998; Choi and Schweizer, 2006; Sun et al, 2014; Chen et al, 2016, 2017). All bacterial strains were cultured in Luria–Bertani (LB) broth (5 g/L Nacl, 5 g/L yeast extract and 10 g/L tryptone, pH 7.4) at 37 ∘ C with agitation at 200 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…P. aeruginosa encodes multiple resistant determinants against fluoroquinolone antibiotics, such as multidrug efflux systems and pyocyanin (Subedi et al, 2018; Fan et al, 2019). However, chromosomally encoded pyocin biosynthesis genes increase the bacterial susceptibility to fluoroquinolone antibiotics (Brazas and Hancock, 2005; Sun et al, 2014; Chen et al, 2017). Ninety percent of P. aeruginosa strains produce pyocins, and each P. aeruginosa strain usually produces multiple types of the pyocins (Michel-Briand and Baysse, 2002; Ghequire and De Mot, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we demonstrated that Orn is required for the T3SS gene expression and bacterial virulence in a mouse acute pneumonia model (18). In addition, we demonstrated that Orn contributes to bacterial resistance to ciprofloxacin by influencing pyocin biosynthesis (19). However, whether Orn is involved in bacterial tolerance to other categories of antibiotics remains unknown.…”
mentioning
confidence: 91%